Identification and quantitation of mucosal and faecal desulfovibrios using real time polymerase chain reaction. Issue 4 (11th March 2004) - Fite, A; Macfarlane, G T; Cummings, J H; Hopkins, M J; Kong, S C; Furrie, E; Macfarlane, S
Abstract : Background: Desulfovibrios produce sulphide, which is toxic to colonic epithelial cells. These bacteria have previously been linked to ulcerative colitis. Traditional methods of culturing these organisms are slow, and often unreliable, while molecular approaches are either non-quantitative or lack sensitivity. Aims: To develop a sensitive method for quantitating desulfovibrios in stools and biopsy tissue, and to investigate the effects of age and disease on these bacteria. Methods: Rectal biopsies were taken from 10 colitis patients and 10 healthy controls. Stool samples were obtained from 10 healthy infants (mean age 1.01 (0.18) years), 10 healthy young adults (26.7 (1.2) years), and 10 healthy elderly people (71.7 (1.2) years). Primers were designed and developed for analysing Desulfovibrio populations in the bowel using real time polymerase chain reaction (PCR). Results: The PCR primers were highly specific for desulfovibrios. Large numbers (approximately 10 6 –10 7 /g) occurred in biopsies in colitis patients and healthy subjects, and no disease related differences were observed. Measurements of mucosal desulfovibrios over 12 months showed marked changes in some patients. Infants (10 6 –10 7 /g) and elderly people (10 7 –10 8 /g) had significantly higher numbers of desulfovibrios in stools compared with young adults (10 5 /g). Conclusions: Real time PCR analysis of desulfovibrios was an efficient and accurate method for studying these potentially harmful microorganisms. Desulfovibrios were ubiquitous in the bowel, irrespective of age. As rectal mucosae were heavily colonised in health and disease, if these bacteria play a role in colitis, some host defect, possibly in sulphide detoxication pathways or in bacterial antigen handling, is required for manifestations of pathogenicity.